Herpes Simplex Type 1 Encephalitis Restricted to the Brainstem in a Pediatric Patient - Juliana Harumi Arita; Jaime Lin; Mirella Maccarini Peruchi; Marcelo Masruha Rodrigues; Luiz Celso Pereira Vilanova (Case Reports in Medicine)
Herpes simplex encephalitis is a potentially fatal infection of central nervous system that typically involves frontal and temporal lobes. Occasionally, it presents an extratemporal involvement and in rarer cases, it is limited to the brainstem. We describe a case of an adolescent who presented with fever, sore throat, and vertigo. Clinical picture evolved to lethargy, tetraparesis, consciousness impairment, and respiratory failure. MRI showed lesions restricted to the brainstem. PCR of CSF was positive for herpes simplex type 1.